Implementasi Pembelajaran IPA Kelas IV Sekolah Dasar Pada Masa Pandemi Covid-19 - Rohmah, Lukiyatur; Sarifah, Iva; Imaningtyas, Imaningtyas (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
The emergence of the COVID-19 pandemic in Indonesia had an impact on learning activities in elementary schools, so they were shifted to online learning. This study aims to find out how to implement science learning during the covid-19 pandemic. This study uses a survey method that is distributed online, the subject of this study is the fourth grade of elementary school with 40 respondents. The results of this study stated that 42% of science material delivery used learning videos more often, then 60% of material combined with practicum was also more often through videos sent by educators and 57.5% of science learning activities more often did assignments, so 90% of respondents stated that science learning during the covid-19 pandemic is still less effective. The conclusion is that in the implementation of science learning during the covid-19 pandemic, there were several difficulties experienced by students so that the learning process became ineffective. Thus, we need a way that is more interesting and supports the implementation of science learning during the COVID-19 pandemic, especially in material combined with practical or direct experiments.